Some Coding Theorems for Nonadditive Generalized Mean-Value Entropies - Satish Kumar; Gurdas Ram; Vishal Gupta (International Journal of Mathematics and Mathematical Sciences)
We give an optimality characterization of nonadditive generalized mean-value entropies from suitable nonadditive and generalized mean-value properties of the measure of average length. The results obtained cover many results obtained by other authors as particular cases, as well as the ordinary length due to Shannon 1948. The main instrument is the 𝑙(𝑛𝑖) function of the word lengths in obtaining the average length of the code.